PENGEMBANGAN KOMPETENSI PEGAWAI DALAM RANGKA PELAYANAN PUBLIK DI LINGKUNGAN KERJA LEMBAGA PENYIARAN PUBLIK RADIO REPUBLIK INDONESIA SAMARINDA - Supriati .; Nur Fitriyah; Anwar Alaydrus (Jurnal Administrative Reform, 2017)
The aim of this study is to describe and analyze Employees’ Competence Development in the Context of Public Service in the Work Environment Public Broadcasting Radio Republik Indonesia Samarinda together with factors that support and hinder the program. This research is descriptive qualitative research that took place in LPP-RRI Samarinda. Primary data taken from interviews with several informants and direct observation. While secondary data are taken from the information or data held by agencies. Drawing conclusions based on the data that is processed by clicking use interactive data analysis models.